Caffeic Acid Phenethyl Ester: A Review of Its Antioxidant Activity, Protective Effects against Ischemia-reperfusion Injury and Drug Adverse Reactions. Issue 13 (2nd October 2016) - Tolba, Mai F.; Omar, Hany A.; Azab, Samar S.; Khalifa, Amani E.; Abdel-Naim, Ashraf B.; Abdel-Rahman, Sherif Z.
Abstract : Propolis, a honey bee product, has been used in folk medicine for centuries for the treatment of abscesses, canker sores and for wound healing. Caffeic acid phenethyl ester (CAPE) is one of the most extensively investigated active components of propolis which possess many biological activities, including antibacterial, antiviral, antioxidant, anti-inflammatory, and anti-cancer effects. CAPE is a polyphenolic compound characterized by potent antioxidant and cytoprotective activities and protective effects against ischemia–reperfusion (I/R)-induced injury in multiple tissues such as brain, retina, heart, skeletal muscles, testis, ovaries, intestine, colon, and liver. Furthermore, several studies indicated the protective effects of CAPE against chemotherapy-induced adverse drug reactions (ADRs) including several antibiotics (streptomycin, vancomycin, isoniazid, ethambutol) and chemotherapeutic agents (mitomycin, doxorubicin, cisplatin, methotrexate). Due to the broad spectrum of pharmacological activities of CAPE, this review makes a special focus on the recently published data about CAPE antioxidant activity as well as its protective effects against I/R-induced injury and many adverse drug reactions.